1980
DOI: 10.1136/adc.55.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella osteomyelitis in childhood. A report of 63 cases seen in Nigerian children of whom 57 had sickle cell anaemia.

Abstract: SUMMARY A review of 63 Nigerian children with salmonella osteomyelitis showed that in all but 2 ofthem the disease occurred in association with HbS either in the homozygous state (57 patients) or in heterozygous combination with other haemoglobins (4 patients). Osteomyelitis was most prevalent during the first 2 years of life, and boys were more often affected than girls. In the majority, multiple sites were involved and lesions were usually bilateral and often symmetrical. Salmonella sp. was isolated from bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(53 citation statements)
references
References 21 publications
1
50
0
1
Order By: Relevance
“…Children with immunodeficiencies such as an impaired reticuloendothelial system or cellular immune response or SCD may have a predisposition. Adeyokunnu et al reported 90% of patients with Salmonella osteomyelitis had SCD in their study [9]. Our patient did not have SCD, but a previous trauma of affected bones or skeletal prostheses can also increase the possibility of Salmonella osteomyelitis [3], as seen in our patient.…”
Section: Discussionsupporting
confidence: 52%
“…Children with immunodeficiencies such as an impaired reticuloendothelial system or cellular immune response or SCD may have a predisposition. Adeyokunnu et al reported 90% of patients with Salmonella osteomyelitis had SCD in their study [9]. Our patient did not have SCD, but a previous trauma of affected bones or skeletal prostheses can also increase the possibility of Salmonella osteomyelitis [3], as seen in our patient.…”
Section: Discussionsupporting
confidence: 52%
“…9,15 The extraordinary susceptibility of patients with SCD to Salmonella osteomyelitis was first described fully in 1951 by Hodges and Holt 15 and has since been confirmed in several studies. 17,18 Over 70% of osteomyelitis seen in our patients with SCD was caused by non-typhoid Salmonella spp. The relative incidence is four times that of Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Over 70% of osteomyelitis seen in our patients with SCD was caused by non-typhoid Salmonella spp. The relative incidence is four times that of Staphylococcus aureus.…”
Section: 15mentioning
confidence: 99%
“…The onset is usually insidious with no acute febrile illness and general reaction. In patients with sickle cell disease the shaft is more commonly involved than the metaphysis, it may be multifocal and frequently the invading organism is salmonella [1]. Cole [3] has classified childhood chronic osteomyelitis in non-specific and specific groups.…”
Section: Discussionmentioning
confidence: 99%